The association between APOA5 haplotypes and plasma lipids is not modified by energy or fat intake: the Czech HAPIEE study - Hubacek, J A; Peasey, A; Kubinova, R; Pikhart, H; Bobak, M (Nutrition, metabolism, and cardiovascular diseases, 2014)
BACKGROUND AND AIMS: Several smaller studies reported interactions between dietary factors and apolipoprotein A5 (APOA5) gene polymorphisms in determination of plasma lipids. We tested interactions between APOA5 haplotypes and dietary intake in determination of plasma triglycerides (TG) and other lipids. METHODS AND RESULTS: Participants (5487 males and females aged 45-69) were classified according to the number (0, 1, 2+) of minor APOA5 alleles (using T-1131 > C; rs662799 and Ser19 > Trp; rs3135506 polymorphisms) and into three groups of low (bottom 25%), medium (26th-75th percentile) and high (top 25%) of intake of total energy and total, saturated and polyunsaturated fats, assessed by food frequency questionnaire. The age-sex adjusted geometric means of plasma TG increased with the number of minor alleles, from 1.57 (standard error 0.01), to 1.79 (0.02) to 2.29 (0.10) mmol/L (p < 0.00001) but TG did not differ between groups with low, medium and high total energy intake (p = 0.251). TG concentrations were highest in subjects with the combination of 2+ minor alleles and the highest energy intake (mean 2.59 [0.19], compared with 1.62 [0.03] in subjects with lowest energy intake and no minor allele) but the interaction between energy intake and APOA5 haplotypes was not statistically significant (p = 0.186). Analogous analyses with total, saturated and polyunsaturated fat intake yielded similar nonsignificant results. Effects of APOA5 and dietary intakes on total and HDL cholesterol were weaker and no interactions were significant. CONCLUSION: In this Slavic Caucasian population sample, we did not detect the hypothesized interaction between common SNPs within the APOA5 gene and diet in determination of blood lipids.
Keywords: Polymorphism; Apolipoprotein A5; haplotypy; Male; Total energy intake; Česká republika; hodnocení stavu výživy; Nutrition Assessment; běloši; Cholesterol; Haplotypes; Aged; mužské pohlaví; senioři; lineární modely; jednonukleotidový polymorfismus; Dietary Fats; triglyceridy; průzkumy a dotazníky; White People; Czech Republic; dietní tuky; cholesterol; Polymorphism, Single Nucleotide; lidé; apolipoproteiny A; ženské pohlaví; Humans; Body Mass Index; Energy Intake; Linear Models; Interaction; apolipoprotein A-V; index tělesné hmotnosti; Triglycerides; energetický příjem; Apolipoprotein A-V; Alleles; Female; Surveys and Questionnaires; alely; lidé středního věku; Apolipoproteins A; Middle Aged